Physical activated carbon from palm kernel shell for carbon brush application - Norasyikin Mohd. Mustapha, 1986-; Abdul Rahim Yacob; Fakulti Sains (2009)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2009